Sarcasm in Digital Discourse: Representation of Public Distrust of Political Institutions on Patinews Facebook Account - Lukman Alfaris; Nova Khairul Anam; Saeful Rohman; Leli Triana (Universitas Negeri Semarang, 2026)
Social media has evolved into a digital public space where people can express opinions, criticism, and dissatisfaction about various political issues. One widely used form of expression is sarcasm, namely the use of sharp, demeaning language to criticize individuals and institutions. This study aims to describe the forms of sarcasm and reveal the representation of public distrust of political institutions in netizen comments on the Patinews Facebook account. The study used a qualitative approach, employing digital discourse analysis and Norman Fairclough's Critical Discourse Analysis framework. The research data consisted of netizen comments on the Patinews post entitled